The Use of Self-Report and Drugs Tests in the Measurement of Illicit Drug Consumpiton - Stephen Pudney
We use data from the New England and Wales Arrestee Drug Abuse Monitoring (NEW-ADAM) programme to assess the validity of self-report measures of illicit drug use and to evaluate the use of alternative drug testing strategies within survey enquiries. Our analysis of the NEW-ADAM data reveals that bio-assay measurements of drug use tend not to be very sensitive to the cut-off levels selected for screening tests, a result that holds for cannabis, cocaine and opiates. We also show that a self-reported history of previous drug use can be used as a way of identifying individuals who are potential under-reporters of current drug use. This suggests a selective drug testing strategy which can reduce dramatically the cost of drug testing without comprising the accuracy of measurements of illicit drug use.Drugs testing; Self-reports; Concordance; Testing Strategies